Adaptability in healthcare buildings: a perspective through Joseph Bracops Hospital - Scialpi, Giulia; Declercq, Joost (Frontiers in Medical Technology, 2023)
The healthcare sector has to face changes happening fast and often in an unpredictable way, such as the epidemiological trends, the advancements of medical technology and processes or the evolving social and economic needs. This results in a frequent need for infrastructures’ retrofitting, with an increasing environmental impact for buildings, which have one of the highest embodied carbon footprints per square meter in the construction sector. As result, the interest in healthcare buildings’ adaptability is growing among researchers and practitioners. After an introduction on the research topic, a focus on the definition of adaptability and the existing assessment models is provided to address the following research question: to what extent are adaptability models effective to evaluate and orient the design of healthcare buildings? A quite varied use of the term adaptability has been found in the literature, as well as a new research trend aiming to establish a link with circularity. Moreover, most of the assessment models do not have a focus and have never been tested on the healthcare sector. An approach to circular and adaptable design is presented through the case study of the Joseph Bracops Hospital (Belgium), which has been submitted for evaluation by the Reversible Building Design protocol developed by Dr. Durmisevic. The evaluation highlights some of the current barriers in the design of adaptable healthcare facilities. Insights for future research are provided to encourage data-collection about the service life of healthcare buildings, to understand if the adaptability of these infrastructures should be monofunctional or transfunctional.